2021
DOI: 10.1590/1678-6971/eramr210082
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Entrepreneurial Passion and Creativity on Entrepreneurial Intentions

Abstract: Purpose: This study aims to analyze the influence of entrepreneurial passion and creativity on entrepreneurial intent. It also examines the mediating role of entrepreneurial self-efficacy between the personal/cognitive variable and entrepreneurial intention. Originality/value: By stressing the importance of cognitive and emotional variables that may influence entrepreneurial intentions among university students (such as creativity and entrepreneurial passion), this study shows the important role that universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 71 publications
3
12
0
6
Order By: Relevance
“…In the case of H2 (the relationship between entrepreneurial passion and entrepreneurial self-efficacy), they are in line with previous research, such as those of Liu et al (2021), Bignetti et al (2021), Norena-Chavez and Thalassinos (2021), Norena-Chavez and Guevara (2020), Taifur et al (2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the case of H2 (the relationship between entrepreneurial passion and entrepreneurial self-efficacy), they are in line with previous research, such as those of Liu et al (2021), Bignetti et al (2021), Norena-Chavez and Thalassinos (2021), Norena-Chavez and Guevara (2020), Taifur et al (2020).…”
Section: Discussionsupporting
confidence: 89%
“…Liu et al (2021) found that entrepreneurial self-efficacy increased in nascent entrepreneurs when entrepreneurial passion was stronger. Bignetti et al (2021) concluded that gender, age, program completed, family background, and family income showed no significant differences when studied together with entrepreneurial self-efficacy and entrepreneurial passion. Norena-Chavez and Thalassinos (2021) concluded that entrepreneurial self-efficacy and passion are positively and significantly related to industrial footwear in a developing country.…”
Section: A) What Is the Relationship Between Entrepreneurial Passion ...mentioning
confidence: 94%
“…Entrepreneurial intention is an individual's tendency to start a business when choosing an occupation, and is considered to be a proximal and immediate predictor of entrepreneurial behavior (Bird and Jelinek, 1988;Bagozzi et al, 1989;Krueger et al, 2000;Majeed et al, 2021). Entrepreneurial passion is the passion experienced by individuals in the entrepreneurial circumstances (Mageau et al, 2009;Perrewe et al, 2013;Cardon and Kirk, 2015;Türk et al, 2020;Yi et al, 2020;Bignetti et al, 2021;Liu et al, 2021). According to the stage of entrepreneurial development, entrepreneurial passion can be divided into the passion for founding enterprises, the passion for discovering opportunities and the passion for developing enterprises (Cardon et al, 2013).…”
Section: Entrepreneurial Calling and Entrepreneurial Role Modelsmentioning
confidence: 99%
“…Therefore, the higher the entrepreneurial passion for new ventures, the more it can give full play to the external environment and the cognitive role of entrepreneurial alertness to guide and stimulate the creative bricolage of the limited resources available and positively promote entrepreneurial opportunity identification. On the contrary, when new ventures lack entrepreneurial passion, their entrepreneurial alertness to the external environment is severely reduced (Bignetti et al, 2021 ). The lack of environmental information prevents new ventures from effectively planning and implementing entrepreneurial bricolage activities (Guo et al, 2016 ), inhibiting entrepreneurial opportunity identification.…”
Section: Theoretical Basis and Research Hypothesesmentioning
confidence: 99%